PENERAPAN TEKNOLOGI DAPUR HIDUP SIAGA STUNTING MELALUI PELATIHAN BUDIKDAMBER DAN BUDIDAYA CHAYA KEPADA IBU BALITA: Implementation Of Ready-To-Use Therapeutic Food Technology Through Budikdamber Training And Chaya Cultivation For Mothers Of Toddlers - Taufiq Firdaus Al-Ghifari Atmadja; Nur Arifah Qurota A’yunin; Neni Neni (Pakis Journal Institute, 2023)
Stunting is a chronic nutritional problem caused by prolonged insufficient intake of nutrients due to inappropriate feeding practices over an extended period. Based on interviews with community health workers and mothers of toddlers in the Karanganyar area, the high prevalence of stunting is suspected to be due to the lack of understanding among the community regarding the importance of nutrition for child growth and development. Therefore, a solution that can be pursued involves the creation of locally sourced complementary feeding (MPASI) that is economically friendly yet rich in nutritional content, through the introduction of the Stunting Alert Kitchen (Dapur Hidup Siaga Stunting) using the budikdamber method and chaya cultivation. The implementation of this solution includes Focus Group Discussions (FGD), Stunting Alert Kitchen training and practice sessions for budikdamber and chaya cultivation, as well as guidance, monitoring, and evaluation. The outcomes of these activities include enthusiastic participation from the attendees. The sessions began with an introduction to chaya cultivation. Cultivating chaya plants is relatively simple as they do not require special treatment. Growing chaya in household gardens can support the household's food security by providing nutritious vegetables, enhancing overall health, and ensuring optimal nutritional intake. The subsequent activity involved budikdamber training. The advantage of budikdamber is its ability to serve as a means of fish cultivation in buckets without the need for pond space. It also allows for hydroponic cultivation of vegetables, which piqued the interest of mothers of toddlers.